FGD Gypsum Litter Effects on Gaseous Losses from a Broiler House - Watts , Dexter B.; Runion, G. Brett; Purswell, Joseph L.; Torbert, H. Allen; Davis, Jeremiah D. (International Journal of Poultry Science, 2019)
Background and Objectives: Greenhouse gas (GHG) emissions are increasing at an unprecedented rate and are expected to double pre-industrial revolution levels within this century. The effects of broiler house management on these emissions are unknown. A study was conducted to examine the effect of FGD gypsum bedding on efflux of NH3, CO2, CH4 and N2O. Materials and Methods: FGD gypsum bedding was compared with pine shavings and pine shaving+FGD gypsum (50:50 mix) and each litter type was either decaked or rotovated after each flock. Flux measurements (CO2, CH4 and N2O) and NH3 concentrations were taken during flocks 4 and 5. Results: Litter treatment had little effect on GHG gas emissions during flocks 4 and 5 but NH3 concentrations tended to be lower with FGD gypsum. Decaking tended to lower NH3 concentration and GHG emissions due to removal of some of the manure material. Conclusion: This first examination of the effects of different litter materials on GHG emissions from broiler houses showed that FGD gypsum can reduce NH3 concentrations without impacting climate change; however, more research is needed to verify these results.